RBIS regulates ribosome biogenesis to affect progression in lung adenocarcinoma - Hongyu Pan; Li Liao; Siwei Xu; Yujian Xu; Wenjun Chai; Xiaoli Liu; Jing Li; Yue Cao; Lei Sun; Qian Liu; Mingxia Yan (Journal of Translational Medicine)
Abstract Background Increased ribosome biogenesis is required for tumor growth. In this study, we investigated the function and underlying molecular mechanism of ribosome biogenesis factor (RBIS) in the progression of non-small cell lung cancer (NSCLC). Methods In our study, we conducted a comprehensive analysis to identify key genes implicated in ribosome biogenesis by leveraging a Gene Set Enrichment Analysis (GSEA) dataset. Subsequently, we performed a comparative analysis of gene expression profiles by utilizing data from the Gene Expression Omnibus (GEO) datasets to ascertain differentially expressed genes (DEGs) between cancerous and adjacent non-cancerous tissues. Through the intersection of gene sets derived from GSEA and GEO, we identified a cohort of ribosome-associated genes that might exert a substantial influence on the progression of lung adenocarcinoma. Following an extensive literature review, we have identified the RBIS gene as an interesting candidate for further investigation. To elucidate the in vitro functional role of RBIS, several assays was employed, including the Transwell migration and invasion assay, wound healing assay, Cell Counting Kit-8 (CCK-8) proliferation assay, and colony formation assay. Subcutaneous and tail vein injection-based lung metastasis xenograft tumor models were used in evaluating the tumorigenic potential, growth, and metastatic spread of lung cancer cells. Flow cytometry analysis was employed to investigate cell cycle distribution and apoptotic rates. Additionally, real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) was utilized to quantify the mRNA expression levels of genes. To comprehensively assess the translational efficiency of nascent proteins, we employed polysome profiling analysis to provide insights into the cellular translational landscape. Furthermore, we quantified global protein synthesis using a fluorescence-based assay to measure protein synthesis rates. The immunofluorescence technology was utilized to study the subcellular reorganization of the nucleolus. We conducted co-immunoprecipitation (Co-IP) assays followed by Western blot analysis to identify potential proteins interacted with RBIS. The half maximal inhibitory concentration (IC50) was used for evaluating the chemosensitivity of lung cancer cells to gemcitabine. Additionally, the colony formation assay was employed to assess the survival and proliferative capacity post-treatment of gemcitabine. Results The database analysis showed that RBIS was upregulated in lung adenocarcinoma, and its high expression was associated with poor prognosis; Knockdown of RBIS significantly inhibited NSCLC cell migration, invasion and proliferation in vitro and xenograft tumor growth and metastasis in vivo. Additionally, knockdown of RBIS led to G0/G1 phase arrest and significantly increased apoptosis in lung adenocarcinoma cells. Mechanistically, downregulation of RBIS significantly decreased the expression of 47S ribosomal RNA (rRNA), a component associated with ribosome assembly. Polysome profiling analysis indicated that RBIS knockdown affected protein translation efficiency, and global protein synthesis assay further verified that RBIS knockdown inhibited synthesis of newborn proteins. Additionally, the ribosomal biogenesis-targeting drugs CX-5461 and the loss of RBIS exhibited synergistic effects in inhibiting cell cycle progression and inducing apoptosis. Furthermore, the ribosomal maturation factor GNL2 was identified as the key downstream regulator of RBIS in ribosome biogenesis. Notably, knockdown of RBIS substantially increased the sensitivity of lung adenocarcinoma cells to the chemotherapeutic drug gemcitabine, highlighting its l role in chemotherapy. Conclusions Collectively, these studies suggested the close involvement of RBIS in the progression of lung adenocarcinoma, providing new insights for targeted therapeutic interventions involving ribosomes.